PENGEMBANGAN MEDIA PERKULIAHAN PKN BERBASIS WEBSITE UNTUK MENINGKATKAN LITERASI BUDAYA DAN KEWARGAAN MAHASISWA PGSD UNIVERSITAS MUHAMMADIYAH SIDOARJO - Fihayati, Zuyyina; Macfhul Indrakurniawan; Ade Eviyanti; Nila Sekardhani Hadian; Septya Bayu Andita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop website-based Civics E-Book lecture media to improve the cultural and civic literacy skills of PGSD students of Muhammadiyah Sidoarjo University. This research was conducted based on the results of research conducted by researchers funded by DRPM Universitas Muhammadiyah Sidoarjo in the 2021/2022 fiscal year with the title